Pengaruh Grup Referensi, Keyakinan Diri, dan Skill terhadap Motivasi Berwirausaha Mahasiswa Universitas Sarjanawiyata Tamansiswa Yogyakarta - Setiyaningtiyas, Windi; Kirana, Kusuma Chandra; Purnamarini, Tri Ratna (Journal of Economics, Bussiness and Management Issues, 2025)
This research aims to identify and analyze the influence of reference groups, self-confidence, and skills on entrepreneurial motivation among students of the Faculty of Economics at Sarjanawiyata Tamansiswa University. This type  of  research  is  quantitative  descriptive. The sample used in this study consists of 115 active students from the Faculty of Economics at Sarjanawiyata Tamansiswa University. The type of data used in this research is quantitative data. The sampling technique employed is non-probability sampling or non-random sampling, specifically using convenience sampling. The data analysis techniques used in this study include data quality tests, classical assumption tests, and multiple linear regression analysis, followed by hypothesis testing (t-test and F-test) as formulated, and then, the analysis of the coefficient of determination (R²). The results of this analysis indicate that, partially, reference groups, self-confidence, and skills have a positive and significant effect on students' entrepreneurial motivation. Simultaneously, reference groups, self-confidence, and skills positively and significantly influence the entrepreneurial motivation of students at the Faculty of Economics, Sarjanawiyata Tamansiswa University.